Aerosol Jet Printed Polymer Composite Electrolytes for Solid‐State Li‐Ion Batteries. Issue 12 (16th October 2019) - Deiner, L. Jay; Jenkins, Thomas; Howell, Thomas; Rottmayer, Michael
Abstract : Solid‐state lithium‐ion (Li‐ion) batteries are a next generation energy storage technology that is able to address the transportation sector's need for increased safety and power density. Realizing this capability requires development of scalable manufacturing methods for solid electrolyte materials and for integration of such materials into battery cells. Herein, the first demonstration of aerosol jet printing is provided, which is a manufacturing‐ready 3D printing technique for fabrication of Li‐ion conducting solid polymer composite electrolytes. Deposition is performed directly on LiFePO4 cathode substrates. Aerosol jet printed electrolytes composed of polyethylene oxide (PEO), lithium difluoro(oxalato)borate (LiDFOB), and alumina nanoparticles are smooth, conformal, and nonporous, whereas those composed of PEO, lithium trifluoromethanesulfonate (LiTriflate), and alumina nanoparticles are conformal and porous. Conductivity of the printed solid polymer electrolytes tracks salt anion identity and concentration. The most conductive printed electrolyte, PEO/LiDFOB/alumina (EO:Li = 10:1), achieves conductivity >1 × 10 −5 S cm −1 at 45 °C. In half cell configuration, batteries with this printed electrolyte can be discharged at C/15 with capacity >85 mAh g −1 at 45 °C and >160 mAh g −1 at 75 °C. The achievement of aerosol jet printed solid polymer composite electrolytes opens a path for scalable manufacturing of solid‐state Li‐ion batteries. Abstract : The first aerosol jet printed Li‐ion‐conducting solid polymer composite electrolyte is achieved, and morphology and conductivity is shown to reflect ink formulation. The most promising formulation produces a 40–50 μm thick smooth and conformal printed solid polymer electrolyte layer with >85 mAh g −1 discharge capacity at 45 °C and >160 mAh g −1 at 75 °C.